2016
DOI: 10.1093/mnras/stw2799
|View full text |Cite
|
Sign up to set email alerts
|

HD 164492C: a rapidly rotating, Hα-bright, magnetic early B star associated with a 12.5 d spectroscopic binary

Abstract: We employ high resolution spectroscopy and spectropolarimetry to derive the physical properties and magnetic characteristics of the multiple system HD 164492C, located in the young open cluster M20. The spectrum reveals evidence of 3 components: a broad-lined early B star (HD 164492C1), a narrow-lined early B star (HD 164492C2), and a late B star (HD 164492C3). Components C2 and C3 exhibit significant (> 100 km/s) bulk radial velocity variations with a period of 12.5351(7) d that we attribute to eccentric bina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…The resulting distance from Gaia EDR3 parallaxes is much closer than previous measurements using spectroscopic parallaxes or extinction mapping. It agrees with the estimate of ∼1.22 kpc made using Gaia DR2 parallaxes by Wade et al (2017). As a comparison, also shown are the histogram of distances of Gaia EDR3 sources meeting the proper motion criterion, and having RUWE and σ π within the limit for our sample.…”
Section: Distance To the Trifid Nebulasupporting
confidence: 89%
“…The resulting distance from Gaia EDR3 parallaxes is much closer than previous measurements using spectroscopic parallaxes or extinction mapping. It agrees with the estimate of ∼1.22 kpc made using Gaia DR2 parallaxes by Wade et al (2017). As a comparison, also shown are the histogram of distances of Gaia EDR3 sources meeting the proper motion criterion, and having RUWE and σ π within the limit for our sample.…”
Section: Distance To the Trifid Nebulasupporting
confidence: 89%
“…We speculate that the magnetic field has a large scale structure that is similar to a simple dipolar configuration and a stable configuration deduced by the long lifetime of the spot (≥ 2.5 yrs). Wade et al (2017) have found a strong magnetic field, on the order of a few kG, in HD 164492C1, which is an early B star similar to ρ Oph rotating in 1.36 days and part of a hierarchical system with other two A/Herbig Ae stars belonging to the Trifid nebula. However, one difference from ρ Oph is that the HD 164492 system is tighter than that of ρ Oph and the origin of the magnetic field in such objects could be associated with binarity and the stellar formation mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…The prototype of a hot magnetic star with a RRM is σ Ori E (Groote & Hunger 1997;Townsend, Owocki & Groote 2005). Several σ Ori E analogues since discovered are: δ Ori C (Leone et al 2010); HD 176582 (Bohlender & Monin 2011); HR 5907 (Grunhut et al 2012a); HR 7355 (Rivinius et al 2013); HD 23478 (Eikenberry et al 2014;Sikora et al 2015); HD 345439 (Eikenberry et al 2014;Wisniewski et al 2015;Hubrig et al 2017); HD 35502 (Sikora et al 2016); HD 164492C (Wade et al 2017).…”
mentioning
confidence: 99%